Pumped storage power station using abandoned mine in the Yellow River basin: A feasibility analysis under the perspective of carbon neutrality - Xi, Furui; Yan, Ruiwen; Shi, Jusong; Zhang, Jinde; Wang, Runping (Frontiers in Environmental Science, 2022)
Greenhouse gas emissions, mainly CO2, lead to global climate change, and the resulting ecological environment problems bring severe challenges to human survival and development. As the world's largest developing country and carbon emitter, China is facing the dual pressure of socio-economic development and carbon emission reduction. In order to cope with global climate change and achieve the goal of carbon neutrality and carbon peak as soon as possible, China needs to accelerate the optimization of energy structure, gradually increase the proportion of renewable energy utilization, and accelerate the solution of the bottleneck problem of renewable energy storage. As an energy basin, the Yellow River Basin is a key demonstration area to promote energy system reform in China. There are a large number of abandoned mines in the Yellow River basin, which provide a new idea to build pumped storage power stations using abandoned mines (PSPSuM) for renewable energy storage. From the perspective of multidisciplinary integration, this study deeply discusses the relevant evaluation principles and technical key points of constructing PSPSuM in the region, and preliminatively carries out the feasibility assessment. The results show that 91 PSPSuM can be built in the Yellow River Basin, with a total installed capacity of 15830 MW, comprehensively considering the aspects of spatial size, spatial structure and space stability.